Smart portable stick - Mohd Hanafi, Muhammad Azrey; Hilmi, Ahmad Aliff; Mohammad Zaidi, Madihah Zahirah; Zulkifli, Siti Aniesya; Mohamad Roseli, Nur Hazwani (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Blind people consists of a large group of people in our society. Losing their eyesight has caused them inconvenience in performing daily tasks. Hence, smart portable stick had been developed in order to increase the life quality of a blind person. The reason why is this product need to be innovate is because of blind people cannot easily recognize obstacles while using normal blind stick. Plus, the existing stick in market make the blind people facing with a problem like they cannot reach to unfamiliar places. Then, this product is to easier blind people to reach unfamiliar destinations or direction. It also to help blind people recognize obstacles that might put in a dangerous situation. Next, this innovation is to help blind people get emergency help quickly and easily. Others, ‘Smart Portable Stick’ is the innovation that not like ordinary that can be found anywhere. This is because it is came with a multiple features and problem solution which is it high technologies that link with mobile phone and portable. Our product is completed with audio to show the direction. This product is useful and impactful for blind people because it is automatically detect the obstacles infront of the person by use of sensor present in the systems. It is great commercial potential because "Smart Portable Stick" are not yet sold anywhere on the market. It also has advanced features and functions as suggested by various reports of current problems faced by visually impaired people.